Peningkatan Pengetahuan dan Perilaku Kesehatan Masyarakat Melalui Pendekatan Keluarga - Khayudin, Bayu Akbar; Alfaqih, Mohamad Roni (Journal of Health Innovation and Community Services, 2022)
COVID-19 is spread from person to person through the same mechanisms as other cold or influenza viruses, face to face contact by sneezing, coughing, or transmitted by direct contact with splashes of phlegm or secretions from an infected person, and by touching contaminated surfaces. virus. Based on the results of data in Bojonegoro Regency on November 2, 2020, there were 677 confirmed cases of Covid-19, 59 active, 551 recovered while 67 people died. The purpose of this community service is to improve the health status of the foster families by providing assistance to families who meet the criteria. This community service method uses a fostered family approach through mentoring and health education about the prevention of COVID-19. The activities carried out are by providing prior socialization to students as implementers or teams who will be involved in the community service program and mapping the locations that will be targeted by the fostered families. Then in the implementation of activities, family assistance is carried out by monitoring the health status of the pre-program to post-program families. The programs or activities provided are socialization and assistance about the importance of preventing COVID-19 and health protocols. The results of this program activity can increase public knowledge regarding COVID-19, prevention of COVID-19 and increase public awareness regarding clean and healthy behavior.